Poland between the Wars, 1918–1939
XIV, 153 p.
Keywords: Incorporating selective papers from a successful conference organised by the Polish Society, this book presents challenging and frequently revisionist views on a variety of controversial themes relating to the interwar Polish Republic, including its struggle over Upper Silesia, the question of national identity and its ethnic minorities, the significance of the Battle of Warsaw, the role of the press and its defence preparations in 1939. The volume thus makes an important contribution to scholarly debate of a crucial period in Poland's recent history.